Caring under pressure: economic social determinants of health influence family caregivers - Radcliffe, Payton; Bolling, S. Alison; Patrick, Julie Hicks (Frontiers in Public Health, 2025)
Health disparities, the unequal onset, severity, and treatment of chronic health conditions, are differentially experienced by adults living in different geographic locations in the United States. Coupled with an earlier onset and more severe symptomatology among patients, family care partners may also experience increased stress related to other place-based disparities, including limited access to care and increased economic challenges. Using data from the 2023 Centers for Disease Control and Prevention’s Behavioral Risk Factor Surveillance System, we examine the influences of caregiver resources, caregiving demands, and place-based factors in a structural equation model aimed at understanding caregiver physical and emotional health. Data from 5,432 family caregivers (Mean age 66 yrs.; 60% female; 10% rural) who provide a range of assistance with personal care tasks (49%) and household tasks (78%) were used in a multigroup analysis examining the unique contributions of rurality to this model of caregiver stress. Although rurality does not differentially increase psychological wellbeing challenges among caregivers, rural caregivers did experience exacerbation of physical health challenges when compared to their urban counterparts. Post hoc analyses are conducted in order to isolate this effect and to inform policy and program recommendations.